2017
DOI: 10.1242/jeb.170514
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptors activate fish feeding behaviour via two distinct functional pathways

Abstract: Benzodiazepines, acting through ionotropic receptors of γ-aminobutyric acid (GABA receptors, GABAR), have been shown to modify feeding behaviour and increase appetite in humans and non-human subjects. However, the cellular and molecular mechanisms that underlie connected short-term behavioural fluctuations are still unclear. In the present study, we used (Prussian carp) as a model organism to research the impact of scantily explored benzodiazepine phenazepam (PNZ) on feeding behaviour and the related molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…GABA is the major inhibitory neurotransmitter in the brain . GABA signaling blockage has been widely demonstrated to activate behavior in vertebrates, including zebrafish. , In comparison, serotonin signaling has more complex and multifaceted functions . Serotonin receptor agonists were reported to increase swimming behavior, such as locomotor activity, and cooperative behavior in fish. , Thus, our observations at the neurotransmitter level are consistent with the altered swimming behavior and, therefore, suggest a reasonable mechanistic explanation at the molecular level.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…GABA is the major inhibitory neurotransmitter in the brain . GABA signaling blockage has been widely demonstrated to activate behavior in vertebrates, including zebrafish. , In comparison, serotonin signaling has more complex and multifaceted functions . Serotonin receptor agonists were reported to increase swimming behavior, such as locomotor activity, and cooperative behavior in fish. , Thus, our observations at the neurotransmitter level are consistent with the altered swimming behavior and, therefore, suggest a reasonable mechanistic explanation at the molecular level.…”
Section: Resultssupporting
confidence: 82%
“…37 GABA signaling blockage has been widely demonstrated to activate behavior in vertebrates, including zebrafish. 41,42 In comparison, serotonin signaling has more complex and multifaceted functions. 43 Serotonin receptor agonists were reported to increase swimming behavior, such as locomotor activity, and cooperative behavior in fish.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nevertheless, our data suggest that CBZ exposure may result in an imbalance between excitatory and inhibitory neurotransmission based upon altered receptor expression as well as biosynthetic enzymes. Taken together, changes in brain GABA are expected to contribute to the persistence of deficiencies in locomotor activity reported in studies using zebrafish [43][44][45].…”
Section: Discussionmentioning
confidence: 93%
“…The Gabra1 receptor subunit is localized at synapses in mature neurons and is structurally critical for the formation of ionic channels [47]. Recent studies have shown that GABA A receptor expression is altered by environmental contaminants, such as phenazepam, which can also lead to abnormal regulation of feeding behavior [44]. Moreover, abat and gad1b, two enzymes involved in regulating glutamate-GABA metabolic pathways, were also inhibited by CBZ exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The alterations previously mentioned, may bring adverse consequences to the species involved, but also to the population due to changes in locomotor activity, which may result in alterations of feeding, sexual and social behavior (Snigirov and Sylantyev, 2018).…”
Section: Discussionmentioning
confidence: 99%